Redução de proteína e suplementação com lisina e metionina em dietas para jundiás (Rhamdia quelen) - Schneider, Thamara Luísa Staudt (2020)
Fish production requires the use of sustainable nutritional strategies. Reduced the level of protein and supplementation with lysine and methionine in diets can optimize weight gain and improve the feeding efficiency of fish. The silver catfish, Rhamdia quelen, has favorable characteristics for captive production. In this study, performance, body composition, metabolism and intestinal morphometry of silver catfish fed with reduced protein level and supplementation with lysine and methionine in the diet were evaluated. The experimental design used was completely randomized, composed of five diets and four repetitions. Five diets were formulated: positive control containing 38% crude protein (CP) (38CP), negative control containing 34% CP (34CP); 34CP diet was supplemented with: lysine (34L); methionine (34M) and lysine plus methionine (34LM). For 63 days, 320 juveniles of silver catfish (initial average weight of 26.33 ± 0.40 g) were kept in a water recirculation system consisting of two biological filters, decantation box, water tank, heating and 20 tanks (250 L). 16 fish/tank were randomly distributed and fed with experimental diets three times a day (8, 13 and 18 hours) until apparent satiety. At the end of the experiment, data on weight and length, blood and tissues (liver, muscle, gills and intestine) were collected for analysis of: composition, blood, biochemistry and morphometry. The data obtained were submitted to one-way ANOVA and the means compared by the Tukey test (P <0.05). The final weight, specific growth rate and condition factor were higher in fish fed the 34LM diet than fish fed the 34PB diet (P < 0.05). The deposition of body protein was higher in fish fed a 34LM diet than fish that received a 38PB diet (P = 0.03). In the fillet, there was lower deposition of lipids in fish fed a 34L diet than in fish fed a 34M and 34LM diet (P < 0.0001). Fish fed the 34LM diet had higher AA content in plasma than fish fed the 34L and 34PB diets (P < 0.0001). The lower villus height was observed in fish fed the 34L diet compared to the 38PB diet (P = 0.02). The number of goblet cells per villus was higher in fish fed the 34M diet compared to 34PB, 34L and 34LM (P < 0.0001). The reduction of 4% of the level of protein in the diet for silver catfish can be accomplished, since the diet is supplemented with lysine and methionine.